Marketing digital para promocionar la tienda blush en la ciudad de Guayaquil - Gómez Ayoví, Verónica del Rocío (2017)
Organizations today are small, medium or large, can not be alien to the current that drags them so to speak to the virtual world, which by the way said, all consumers of goods or services are required to access, are these of different condition, and therefore, must be entered through a web page, application, or simply through the so-called social networks, to the benefits, purchases, consultations, etc., in this sense, it can be asserted that who is not in the order of this current, simply does not exist, companies must worry about trends, what markets currently have to meet their needs. This is the case of Blush, a retail for modern women, who accepts the challenge of entering the web to promote their products but in an innovative way in their sector, since similar stores have not yet done so and for both have remained in the lethargy, allowing or leaving a gap of opportunity for the store in question to resolutely seek to conquer the market of technological women who want the same benefits but from the current virtual platform; obtain timely information, recreate, find out what new your favorite brands have to inform them, getting to buy with some application, simplifying the previous process of going to the store, ask for a sales clerk, go to the cashier and pay to take the product purchased; all this is minimized, reducing the burden of inconvenience for the buyer, who can now access the same process but from the comfort of your home, office, work, or your cell phone……..